The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.5223/kjpgn.2010.13.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Melanosis Coli Associated with Aloe Consumption in a Child

Abstract: Melanosis coli is described as a black or brown discoloration of the mucosa of the colon. Such a discoloration is largely due to pigment granule deposition in macrophages in the colonic mucosa, which arises from anthraquinone-containing laxative abuse. Melanosis coli has usually been reported in the elderly. We present the first case of melanosis coli associated with aloe consumption in a Korean child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In China, the MC incidence has presented an increasing trend with an aging population and the changes in diet composition and living environment. The detection rate in our study has exhibited a yearly rising trend, with a younger onset age as reported before ( Shim & Lee, 2010 ). The MC incidence rate is around 10% or higher in Western nations ( Thompson & Heaton, 1980 ), whereas the reported detection rate in China is significantly lower (1.78% in this study).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In China, the MC incidence has presented an increasing trend with an aging population and the changes in diet composition and living environment. The detection rate in our study has exhibited a yearly rising trend, with a younger onset age as reported before ( Shim & Lee, 2010 ). The MC incidence rate is around 10% or higher in Western nations ( Thompson & Heaton, 1980 ), whereas the reported detection rate in China is significantly lower (1.78% in this study).…”
Section: Discussionsupporting
confidence: 77%
“…Aging is an important contributor to cell apoptosis, leading to evidently weakened capability of toxin metabolism, which can indirectly increase MC detection rate in middle-aged and elderly populations considering their slower metabolism ( Devons, 2002 ). Middle-aged and elderly people are prone to constipation ( Shim & Lee, 2010 ), which causes the prolonged duration of fecal retention in the colon and thus accelerates the absorption of toxins by colonic mucosa and stimulates hyperplasia, giving rise to an increased detection rate of colonic polyps and neoplasm. These lines of evidence might partially explain why the detection rates of MC concomitant diseases are higher than those of non-MC patient due to the aging-related pathogenesis of these benign and malignant disorders, such as polyp, inflammation, cancer, and diverticula.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations